Violence: Constructing an Emerging Field of Sociology - Hartmann, Eddie (International Journal of Conflict and Violence (IJCV), 2017)
Recent research in the social sciences has explicitly addressed the challenge of bringing violence back into the center of attention. This has generated substantive progress in terms of both theoretical debate and methodological approaches. However, there is a significant lack of research applying non-reductionist methodological approaches that can, at the same time, be grounded in a theoretical approach to violence as a research subject in its own right. This focus section seeks to address this research gap by strengthening the dialogue between different bodies of literature that pursue disparate strategies of delineating “violence” as the subject of an emerging field of sociology. By synthesizing these literatures, the focus section aims to draw upon insights from social theory and recent developments in the sociology of violence on the one hand, and combine methodological approaches that transcend both micro- and macro-reductionist accounts on the other. In doing so, it offers analytical perspectives for coming to terms with one of the most conspicuous shortcomings in social scientific appraisals of violence: the tendency to treat it as a primarily moral or political problem, instead of conceiving violence as a social fact.